(untitled) (Research, Society and Development, 2022)
The biomaterials, after implanted, remain in contact with the body fluid, which contributes to the corrosion of the materials, compromising their integrity in some types of biomaterials. This work aims to study the corrosion resistance of titanium when subjected to simulated body fluid (SBF). Grade 2 cp titanium samples were anodized with 1M H3PO4 and 1M H3PO4 + 0.15% HF w/v electrolyte at 10 V for 30 minutes. The hybrid coatings are composed of the alkoxide precursors of methacryloxypropyltrimethoxysilane (MPTS) and tetraethoxysilane (TEOS). Non-anodized and anodized samples were coated with the hybrid coating. The coating was analyzed using Fourier Transform Infrared Spectroscopy (FTIR) and thermogravimetry analysis (TGA). The samples were analyzed with Scanning Electron Microscopy (SEM), contact angle, potentiodynamic polarization, Open Circuit Potential (OCP) and Electrochemical Impedance Spectroscopy (EIE). The results showed that the deposition of the hybrid coating on the anodized samples was not effective as expected, since the deposited film showed irregularities, indicating better corrosive behavior of the only anodized samples.